2017
DOI: 10.1111/1756-185x.13056
|View full text |Cite
|
Sign up to set email alerts
|

Five factor score of more than 1 is associated with relapse during the first 2 year‐follow up in patients with eosinophilic granulomatosis with polyangiitis

Abstract: In this study, FFS at diagnosis was associated with relapse and FFS ≥ 1 was the independent predictor of relapse during follow-up for more than 2 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…In this study, BVAS at diagnosis ≥16 could not predict all‐cause mortality in patients with AAV. Whereas, patients with FFS (2009) at diagnosis ≥2 exhibited the higher all‐cause mortality rate than those without during follow‐up ( P = .001), which is compatible with our previous study . On the other hand, MVIA at diagnosis ≥1.35 was significantly associated with all‐cause mortality.…”
Section: Discussionsupporting
confidence: 89%
“…In this study, BVAS at diagnosis ≥16 could not predict all‐cause mortality in patients with AAV. Whereas, patients with FFS (2009) at diagnosis ≥2 exhibited the higher all‐cause mortality rate than those without during follow‐up ( P = .001), which is compatible with our previous study . On the other hand, MVIA at diagnosis ≥1.35 was significantly associated with all‐cause mortality.…”
Section: Discussionsupporting
confidence: 89%
“…The mean FFS was 0.9, and a FFS of 1.0 was calculated as a cut-off to predict relapse of EGPA by a receiver operator characteristic curve. Finally, we demonstrated that relapse was more frequent in patients with FFS ≥1 than those with FFS <1 (68.8% vs. 7.1%, relative risk 28.6) 34…”
Section: Predictive Factors For Prognosis In Korean Patients With Egpamentioning
confidence: 74%
“…Proteinuria (>1 g/day) was significantly more often observed in both MPO-ANCA-positive and PR3-ANCA-positive patients than in ANCA-negative patients (27.3% vs. 6.3% and 66.7% vs. 6.3%, respectively). In addition, MPO-ANCA-positive patients with EGPA showed a higher relapse rate than ANCA-negative patients with EGPA (54.6% vs. 25.0%) 34. Taking the results of the two previous studies together, in Korean patients with EGPA, ANCA positivity may be associated with skin and renal involvement for EGPA at diagnosis and with the occurrence of relapse during follow-up.…”
Section: Comparison Between Anca-positive Versus Anca-negative Egpamentioning
confidence: 76%
“…Also, older age, diagnosis at earlier stage, less cutaneous involvement, more respiratory involvement, high C-reactive protein (CRP), and more generalized symptoms were observed in good responders. Meanwhile, in another study, Kim, et al42 investigated initial variables associated with relapse during follow-up in Korean patients with EGPA. They first obtained the optimal cut-off of FFS to predict relapse of EGPA as 1.…”
Section: Predictors At Diagnosis Of Prognosismentioning
confidence: 99%